An empirical investigation of efficiency in Indian banks: pre and post Global Financial Crisis - Gao, Yining (2016)
The purpose of this paper is to estimate the cost efficiency of commercial banks in India before (0.75), during (0.75) and after (0.63) the Global Financial Crisis, and then make a comparison with each other, found that the cost efficiency has a downward trend from 2003 to 2014. The main used methodology is Stochastic Frontier Approach (SFA) with a serious of tests to support the SFA, such as the test of likelihood of ratio which used to test the inefficiency of SFA.